Development of oral curcumin based on pH-responsive transmembrane peptide-cyclodextrin derivative nanoparticles for hepatoma. (1st February 2022) - Wei, Tiantian; Zhang, Yin; Lei, Meng; Qin, Yanru; Wang, Zhongjie; Chen, Zhimeng; Zhang, Liefeng; Zhu, Yongqiang
Abstract: Herein, a pH-responsive cyclodextrin derivative (R6H4-CMβCD) with cell-penetrating ability was successfully synthesized, and curcumin-loaded nanoparticles (R6H4-CMβCD@CUR NPs, RCCNPs) were developed to improve its efficacy in hepatoma. RCCNPs could improve the cell uptake compared with CMβCD@CUR NPs (CCNPs) and were internalized into cells mainly through endocytosis mediated by reticulin and macropinocytosis. Furthermore, the accumulation of RCCNPs in hepatoma cells at pH 6.4 was higher than that at pH 7.4, indicating a pH-responsive uptake. Additionally, RCCNPs could escape from the lysosomes via the "proton sponge effect", and a high apoptosis rate was detected. Importantly, in vivo experiments revealed that orally administered RCCNPs could exert excellent anti-cancer effects in tumor-bearing mice. Hematoxylin-eosin staining did not show significant histological changes in the major organs. Thus, our findings indicate the potential of R6H4-CMβCD as a nanopharmaceutical material, and RCCNPs as an effective delivery system for oral curcumin in cancer management.